SISTEM INFORMASI PENGOLAHAN DATA SKRIPSI PADA AKADEMI KEPERAWATAN JAMBI YAYASAN TELANAI BHAKTI - Nilawati - (JURNAL AKADEMIKA)
Nursing Academy Jambi is one that requires the existence of a functioning information system for data processing and effective student thesis efficient. In terms of software design, the authors developed a web based information systems with the help Framwork CodeIgniter, because in the CodeIgniter all php functionsand libraries that there had been bundled into a single unit a complete package. For the development of dataand information related to this research obtained through field study and study the literature by searching for relevant sources, with the development of the technology will be adapted to better performance for application developers